PENINGKATAN MOTIVASI BERPRESTASI DENGAN MENGGUNAKAN LAYANAN BIMBINGAN KELOMPOK PADA SISWA KELAS IX SMP NEGERI 1 LIWA TAHUN PELAJARAN 2012/2013 - Umi Salamah; Yusmansyah Yusmansyah; diah utaminingsih (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The problem in this research is the student Achievement Motivation that low. The problem of this study "Are Able Students Achievement Motivation Boost Using Tutoring Services Group In Class IX students of SMP Negeri 1 Liwa West Lampung academic year 2012/2013? The purpose of this study to determine the increase in achievement motivation through group guidance services to the students grade IX SMP Negeri 1 Liwa West Lampung.The method used in this study with a design method of quasi eksperimen, one group pretest-posttest design. . Subjects in the study of eight students with low achievement motivation. Data collection techniques in this study using a scale of achievement motivation, and supported by the observation.The results showed that students' achievement motivation can be enhanced by using group guidance services, as evidenced by the results of the data analysis of achievement motivation as pre-test and post test scores obtained Zhitung= -2.521 and Ztabel = 4, Zhitung Ztabel, then Ho is rejected and Ha accepted, it means there is an increase in achievement motivation before and after a given group counseling services to students grade IX liwa SMP Negeri 1 Liwa West Lampung year 2012/2013.The conclusion in this study is an increase in achievement motivation between before given guidance services group after group counseling services provided to the students grade IX SMP Negeri 1 Liwa West Lampung school year 2012/2012. This means that achievement motivation can be enhanced through group guidance services.Advice can be given (1), To Students should follow the guidance service groups if difficulties in raising achievement motivation, so that students can get a better performance. (2) To the counseling teacher should establish good communication with the entire school community, so that the problem-that exist in students' experiences to be resolved. (3) To the researchers should be able to conduct research using the services, approach, and the same technique but with a different problem, and the same subjects.Keywords: Achievement Motivation, Tutoring Services Group